PENGARUH KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SEMESTER GANJIL SMAN 2 SEKAMPUNG T.P 2016/2017 - Harviana, Riza; Partono, Partono; Alarifin, Dedy Hidayatullah (Universitas Muhammadiyah Metro, 2023)
The research was correlational ex-post facto research to discover the influence of emotional intelligence through physics study results of SMA Negeri 2 Sekampung class X students 2016/2017 time period which consisted as much as nine classrooms. Sample gathering was use Cluster Random Sampling techniques, choosen samples was Siswa Kelas X.MIA.1 which consists as much as 30 students. Data gathering were performed with two instruments, they are emotional intelligence questionnaire which consists as self awareness, self control, self motivation, empathy and social skills and study results which consists as multiple choice and essay test. Inferential analysis results shown that self awareness, self control, self motivation, empathy and social skills simultaneously affected significantly through physics study results of class X.MIA.1 SMA Negeri 2 Sekampung students, with regression equation Y = 0,90X-39,01 with coefficient R2 = 0,94 %. From analysis it can be concluded that self awareness, self control, self motivation, empathy and social skills affects positively through physics study results of class X.MIA.1 SMA Negeri 2 Sekampung students.